2019
DOI: 10.7554/elife.43944
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory module controlling stress-induced cell cycle arrest in Arabidopsis

Abstract: Cell cycle arrest is an active response to stresses that enables organisms to survive under fluctuating environmental conditions. While signalling pathways that inhibit cell cycle progression have been elucidated, the putative core module orchestrating cell cycle arrest in response to various stresses is still elusive. Here we report that in Arabidopsis, the NAC-type transcription factors ANAC044 and ANAC085 are required for DNA damage-induced G2 arrest. Under genotoxic stress conditions, ANAC044 and ANAC085 e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
113
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 57 publications
6
113
0
1
Order By: Relevance
“…The down-regulation of CDKB2;1 in response to DNA damage could thus result from the concomitant degradation of the protein by the APC/C and repression of the CDKB2;1 gene by Rep-MYB3Rs. Very recently, the ANAC044 and ANAC085 transcription factors, the two SOG1 closest relatives that are also SOG1 targets (Ogita et al, 2018), were reported to promote rep-MYB3R accumulation in response to DNA damage (Takahashi et al, 2019). Genetic analysis showed that ANAC044 and ANAC085 function in the same pathway as SOG1 to control cell cycle arrest through rep-MYB3R accumulation but not activation of SMR genes or DNA repair genes.…”
Section: Main Players In Ddr Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The down-regulation of CDKB2;1 in response to DNA damage could thus result from the concomitant degradation of the protein by the APC/C and repression of the CDKB2;1 gene by Rep-MYB3Rs. Very recently, the ANAC044 and ANAC085 transcription factors, the two SOG1 closest relatives that are also SOG1 targets (Ogita et al, 2018), were reported to promote rep-MYB3R accumulation in response to DNA damage (Takahashi et al, 2019). Genetic analysis showed that ANAC044 and ANAC085 function in the same pathway as SOG1 to control cell cycle arrest through rep-MYB3R accumulation but not activation of SMR genes or DNA repair genes.…”
Section: Main Players In Ddr Signalingmentioning
confidence: 99%
“…Genetic analysis showed that ANAC044 and ANAC085 function in the same pathway as SOG1 to control cell cycle arrest through rep-MYB3R accumulation but not activation of SMR genes or DNA repair genes. To date, it remains unclear how ANAC044 and ANAC085 modulate Rep-MYB3R protein levels, as they do not directly target Rep-MYB genes, but this pathway could involve the regulation of proteins involved in the degradation of Rep-MYBs such as F-box proteins (Takahashi et al, 2019). Figure 2 summarizes how DDR triggers cell cycle arrest either in S phase or in G2 phase, and can lead to cell differentiation and endoreduplication.…”
Section: Main Players In Ddr Signalingmentioning
confidence: 99%
“…The SOG1 direct targets include genes implicated in response to abiotic stresses and pathogen infection ( Ogita et al., 2018 ). Two of SOG1 targets, ANAC044 and ANAC085 , are its closest relatives in the NAC TF family and were suggested to also participate in SOG1-mediated induction of stem cell death ( Takahashi et al., 2019 ). However, it is not clear which key downstream PCD effectors are controlled by SOG1/ANAC008 signaling.…”
Section: Nac Transcription Factorsmentioning
confidence: 99%
“…Recently, two independent studies have demonstrated that SOG1 regulates the expression of almost all the genes that are induced when DNA is damaged, including other transcription factors from the same family (Bourbousse et al, 2018; Ogita et al, 2018). Now, in eLife, Masaaki Umeda and colleagues from the Nara Institute of Science and Technology, the RIKEN Center for Sustainable Resource Science and the RIKEN Cluster for Pioneering Research – with Naoki Takahashi as first author – report on the roles of two of these SOG1-like transcription factors, ANAC044 and ANAC085 (Takahashi et al, 2019).…”
mentioning
confidence: 99%
“…If stabilized, these proteins maintain the cells in the phase just before division (G2/M arrest) by binding to and repressing the genes essential for cell division to proceed. It is still unclear how Rep-MYBs are stabilized, or how SOG1 and ANAC044/ANAC085 may trigger cell death (Takahashi et al, 2019).…”
mentioning
confidence: 99%